Ecophysiological and growth characters of ten woody plant species in determining their carbon sequestration - RIDESTI RINDYASTUTI; DIAH RACHMAWATI; RETNO PENI SANCAYANINGSIH; TITUT YULISTYARINI (Society for Indonesian Biodiversity, 2018)
Rindyastuti R, Rachmawati D, Sancayaningsih RP, Yulistyarini T. 2018. Ecophysiological and growth characters of ten woody plant species in determining their carbon sequestration. Biodiversitas 19: 660-669. Tree planting and ecosystem restoration is one of mitigation program of global climate change scheme to reduce CO2 in the atmosphere by sequestering carbon. Carbon storage in the living plant varies among species due to ecophysiological and growth characters of their photosynthesis. Ecophysiological properties of tropical plant species related to carbon sequestration was lack of investigation. The study in this area will be the significant knowledge contribution to C-sink project especially species-level management which has been agreed globally and nationally. The objectives of this research were to study the ecophysiological and growth factors affecting carbon sequestration and to select plant species with high carbon sequestration using 16 months-old-seedling of ten woody plant species. Biomass, carbon storage, the whole plant photosynthetic capacity, total chlorophyll content, stomatal index, and Leaf Area Index (LAI) were significantly different among species. The LAI, total chlorophyll content, whole plant photosynthetic capacity, stem height and stem diameter were positively correlated to biomass and carbon storage. Multivariate correlation test (P>0.05) revealed that the total of chlorophyll content was the ecophysiological factor most contributes to carbon sequestration. The total of chlorophyll content correlates to the stem height, while the whole plant photosynthesis correlates to leaf area in determining plant carbon sequestration. Moreover, two mangrove species, H. littoralis and B. asiatica have the highest carbon sequestration among species studied. For priority in tree planting program in dry lowland habitats, the local species, i.e., S. cumini and D. discolor were more recommended than any others species observed in this study.